Australian paramedic students' mental health literacy and attitudes towards mental health. Issue 1 (11th October 2021) - King, Shannon C.; Rebar, Amanda L.; Oliveri, Paul; Stanton, Robert
Abstract : Purpose: Australian paramedics regularly encounter patients experiencing mental illness. However, some paramedics hold negative attitudes towards the use of emergency services in providing care for these patients. Thus, the purpose of the present study was to examine the mental health literacy (MHL) of Australian paramedic students, and the training and experiential factors associated with MHL. Design/methodology/approach: A cross-sectional online survey was delivered to paramedic students across Australia. A total of 94 paramedic students completed the survey examining MHL, mental health first aid (MHFA) intentions, confidence in providing help, personal and perceived stigma and willingness to interact with a person experiencing mental illness. Findings: Participants generally had poor MHFA intentions in spite of good recognition of mental health disorders and good knowledge about mental health. Participants also demonstrated low stigmatising attitudes towards mental illness; however, they expressed a lack of willingness to interact with a person experiencing mental illness. Originality/value: Our findings propose a combination of work-based experience and specific MHFA training may be beneficial to paramedic students to improve care for patients experiencing mental illness.